Determining the Relation between the Business Environment and Companies Solvency Factors in the Post – crisis Period - Kiyak, Deimena; Pranckevičiūtė, Linara (Ekonomika, 2017)
In scientific literature, there aren’t clearly enough formulated reasons behind causing the solvency component elements changes that would help all companies to prepare for possible insolvency changes. Methods of analysis evaluate following variables: corporate income flows, liabilities amounts, short-term and long-term changes in assets, capital amount, their relative indicators. However, little attention is given to external environmental factors affecting the development of these indicators. The aim of this research is to establish the impact of business environmental factors for companies’ solvency indicators. The business environmental impact assessment seeks to determine just the external – macroeconomic business environment influence for companies’ solvency changes. After identifying the key changes of business environment factors and basic companies’ solvency trends, variables were calculated the dependency was expressed in Pearson correlation coefficients. The evaluation of environmental factors, the main solvency indicators in the sector of warehousing and transport services companies and of the correlation relation determined a statistically significant relationship between companies’ solvency and gross domestic product, inflation, the tax burden, shadow economy, corruption control, number of companies in the sector and interest rate changes. The study identified following dependencies: interest rates, the growth of inflation reduces the debt-to equity ratio, the decrease of the extent of shadow economy and the growth of corruption control increases companies’ debt ratio value, an increased number of companies reduces companies’ debt ratio values. The received statistical relationships and their evaluation of the reliability confirmed the study hypothesis about the statistical significance of the business environment economic factor effect for companies’ solvency changes.
Keywords: warehousing and transportation services sector; the company’s solvency; business environment factors; dependency of variables; Pearson correlation coefficients